Strategi Pemasaran Kopi Pakuwon Dengan Metode Analytical Hierachy Process (AHP) - Anjaswari, Melinda; Sukmawani, Reny; Astutiningsih, Endang Tri (Universitas Galuh, 2024)
Pakuwon coffee is a coffee product produced from planting in an experimental garden owned by the Industrial and Refreshing Plant Agricultural Instrument Standardization Agency (BSIP-TRI) which has the opportunity to be developed. Pakuwon coffee produced by BSIP-TRI generally has not implemented an optimal marketing strategy and its existence is not well known by the wider community, so an appropriate marketing strategy is needed to support the success of this Pakuwon coffee product. Data analysis uses the AHP (Analytical Hierarchy Process) method, from the total calculation using the AHP method, the recommendation for choosing the best marketing strategy for Pakuwon coffee is comprehensive marketing management (market management, marketing mix, field surveys) with the highest score of 0.36 , then criterion C or continuous product research and development with a value of 0.34 and finally criterion B or building a continuous quality raw material procurement system (GAP, GPP) with a weight value of 0.29. The use of the AHP method is considered to be able to determine the selection of the best marketing strategy for Pakuwon coffee owned by BSIP-TRI.